(untitled) (Islamic Sciences Journal, 2023)
Abstract Atheism is not a new problem, rather its existence starts from the beginnings of humanity, and it covers each and every thought related to denying the existence of the Creator of this universe, Glory be to Him, whether it was with the forerunners of secularism or with those who came after them from the Communists and Marxists. And dealing with it superficially, the Western terms falling under secularism, modernity and freedom are terms that serve external parties whose goal is to strike religious beliefs. The prevention of suspicions by rooting the sense of faith in the Muslim community through absolute faith in Allah Almighty is the best protection from the danger of atheism and the suspicions that are raised against the religion. The duty of the official authorities in Islamic countries is to make special channels well prepared to repel suspicions and what is raised by the enemies of the religion, to be an explanation for the people for fear of falling into these suspicions. The Holy Qur’an and the Prophet’s Sunnah are the fortified shield for every believer Muslim if he reflects on the Qur’an and the purified Sunnah. The relationship of religion with science is a strong one; it is not like what is ranged by the enemies of religion. Rather, the Holy Qur’an urges learning, reflection and induction. Calling to Allah or going to an intellectual, doctrinal and moral decline, Allah forbid.